(Microflora Involved in Spontaneous Retting Fermentation of Cassava and Physical Charcteristics of the Flour) - Ramadhani Meutia, Yuliasri; Hawani Lubis, Enny (Balai Besar Industri Agro, 2011)
The studies about bacteria which involved during retting (fermentation) of cassava are still in indonesia .the aim of this research is to study about the microflora which involved during retting of cassava and also to explore the effect of this spontaneous upon the amylograph properties on the fermented cassava flour. the fermentation process run for 4 days, MRSB /MRSA used as isolation media then the isolates identified using API@ 50 CHL .the result showed that lactobacillus plntarum dominated as microflora which involved on the 1 st and 2 nd day ,and on the 3 ed day the fermentation of cassava was dominated by lactobacillus delbrueckii spp delbrueckiion the last day of fermentation lactococcus lactis ssp lactis was dominated .increase in fermentation time has also increased the stability of paste which was investigated of maximum viscosity and gel strength in the fermentation pf cassava flour .